Pengembangan Buku Suplemen Intervensi Life Skill Berbasis STEAM Bagi Anak Berkebutuhan Khusus di Sekolah Dasar Inklusi - Hamidaturrohmah; Muh Muhaimin; Aniatus Sholikhah; Daniela Arnesti Nailufar (Indonesian Journal of Humanities and Social Sciences, 2023)
The optimal development of children with special needs in inclusive elementary schools has not been fully realized despite existing interventions. This research aims to depict the development of a supplementary book focusing on life skills, based on STEAM (Science, Technology, Engineering, Arts, Mathematics), tailored for children with special needs in inclusive elementary schools. This study adopts the Plomp model with four phases: initial investigation, design, realization, and test, evaluation, revision. The research findings indicate that the developed supplement book for life skills based on STEAM is highly suitable for use. Expert validation scores reached 90 and 97, categorizing them as very valid. The accompanying teacher's response scored 90, falling into the very good category. In the mentoring practice trial, scores were obtained for dyslexia (88), intellectual disability (86), Down syndrome (80), and Asperger's syndrome (78). Consequently, it can be concluded that this STEAM-based life skills mentoring book is highly suitable as an intervention guide for children with special needs, enabling them to enhance their life skills to the fullest extent.